Interactive Media Design with Blelozz Cartoons as an Alternative to Toddler Dependence on Gadgaet at Made Blez Studio - Agung Mulyawan, I Dewa Gede; Sudika Negara, I Nengah; Arya Putraka, Agus Ngurah (Program Studi Desain Komunikasi Visual, 2024)
Gadgets are one of the technological developments that are used equally in all age groups, including children under 5 years old. The use of gadgets in toddlers can interfere with the natural development process. The excessive application of gadgets without a portion that is balanced with direct interaction from parents and their environment causes dependence in children which of course affects them physically and psychologically. The descriptive qualitative method was chosen because the process of obtaining data is focused on problems based on facts carried out by observation, interviews, literature and supported by documentation obtained directly in the field. From the observations that have been made with the aforementioned methods, it is found that gadget addiction is caused by a lack of playing facilities and parenting provided by parents, so the design of interactive media is considered appropriate as an alternative to replace toddlers' dependence on gadgets.